2019
DOI: 10.1161/circheartfailure.118.005517
|View full text |Cite
|
Sign up to set email alerts
|

Heart Transplantation With Donation After Circulatory Death

Abstract: Heart transplantation remains the preferred option for improving quality of life and survival for patients suffering from end-stage heart failure. Unfortunately, insufficient supply of cardiac grafts has become an obstacle. Increasing organ availability with donation after circulatory death (DCD) may be a promising option to overcome the organ shortage. Unlike conventional donation after brain death, DCD organs undergo a period of warm, global ischemia between circulatory arrest and graft procurement, which ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 84 publications
0
36
0
1
Order By: Relevance
“…Compared with exsanguination, an entire circulatory load is unavoidable for the DCD hearts during hypoxia caused by asphyxiation (30). Besides, hypoxic pulmonary vasoconstriction following asphyxiation results in right ventricular dilatation and more damage to hearts compared with exsanguination (3,31). To induce asphyxiation, Quader et al terminated the ventilation support following paralyzing skeletal muscles with muscle relaxants (32,33), while Tolboom et al chose to transect the diaphragm (12,13).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared with exsanguination, an entire circulatory load is unavoidable for the DCD hearts during hypoxia caused by asphyxiation (30). Besides, hypoxic pulmonary vasoconstriction following asphyxiation results in right ventricular dilatation and more damage to hearts compared with exsanguination (3,31). To induce asphyxiation, Quader et al terminated the ventilation support following paralyzing skeletal muscles with muscle relaxants (32,33), while Tolboom et al chose to transect the diaphragm (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Aceros et al and Kearns et al declared circulatory death and initiation of warm ischemia when asystole or systolic blood pressure below 30 mmHg was observed (14,(16)(17)(18). Niederberger et al suggested that a clear definition of circulatory arrest and the timing of warm ischemia was significant because damage for the grafts before procurement might vary dramatically according to the different definitions of the warm ischemia start time (3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only curative therapy for end-stage heart failure is heart transplantation. However, it is an invasive procedure and the demand greatly exceeds the limited number of donor hearts available [ 3 ].…”
Section: Introductionmentioning
confidence: 99%